Evaluation of compliance to national nutrition policies in summer day camps. Issue 9 (9th June 2014) - Tilley, Falon; Beets, Michael W; Jones, Sonya; Turner-McGrievy, Gabrielle
Abstract : Objective: The National Afterschool Association (NAA) standards specify the role of summer day camps (SDC) in promoting healthy nutrition habits of the children attending, identifying foods and beverages to be provided to children and staff roles in promoting good nutrition habits. However, many SDC do not provide meals. Currently, national guidelines specifying what children are allowed to bring to such settings do not exist, nor is there a solid understanding of the current landscape surrounding healthy eating within SDC. Design: A cross-sectional study design using validated measures with multiple observations was used to determine the types of foods and beverages brought to SDC programmes. Setting: Four large-scale, community-based SDC participated in the study during summer 2011. Subjects: The types of foods and beverages brought by children ( n 766) and staff ( n 87), as well as any instances of staff promoting healthy eating behaviours, were examined via direct observation over 27 d. Additionally, the extent to which current foods and beverages at SDC complied with NAA standards was evaluated. Results: Less than half of the children brought water, 47 % brought non-100 % juices, 4 % brought soda, 4 % brought a vegetable and 20 % brought fruit. Staff foods and beverages modelled similar patterns. Promotion of healthy eating by staff was observed <1 % of the time. Conclusions: Findings suggest that foods and beverages brought to SDC by children and staff do not support nutrition standards and staff do not regularly promote healthy eating habits. To assist, professional development, parent education and organizational policies are needed.